Measurement of the charge asymmetry in top-quark pair production in proton-proton collisions at √s=7 TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; Ghete, V; et al. (2012)
The difference in angular distributions between top quarks and antiquarks, commonly referred to as the charge asymmetry, is measured in pp collisions at the LHC with the CMS experiment. The data sample corresponds to an integrated luminosity of 1.09fb -1 at a centre-of-mass energy of 7 TeV. Top-quark pairs are selected in the final state with an electron or muon and four or more jets. At least one jet is identified as originating from b-quark hadronization. The charge asymmetry is measured in two variables, one based on the pseudorapidities (η) of the top quarks and the other on their rapidities (y). The results ACη=-0.017±0.032(stat.)-0.036+0.025(syst.) and ACy=-0.013±0.028(stat.)-0.031+0.029(syst.) are consistent within uncertainties with the standard-model predictions. © 2012 CERN.